Copyright Protection Is One Of The Most Important Issues In Art - Alimov Nodir Yunusovich (Peerian Journals Publishing, 2022)
The production of counterfeit products and the fight against its sale, the observance of the rights of authors and copyright holders is one of the important issues not only in jurisprudence, but also in art history.
Keywords: copyright; property rights; personal non-property rights; intellectual property agency